2012
DOI: 10.1590/s1516-14392012005000002
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the titanium oxide morphology and composition by a combined chemical-electrochemical treatment on cp Ti

Abstract: A combined chemical-electrochemical oxidation method to obtain porous bioactive TiO 2 films on titanium is reported. In this case, a titanium chemical pre-etching followed by the micro-arc oxidation (MAO) treatment is proposed and optimized, to obtain a high-roughness and porous surface which benefits the titanium/bone integration. The MAO treatment at various rates (different current densities) allowed to define the influence of the oxide growth rate on the surface morphology and to design the best features f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…On the other hand, it is the studies of the mechanical properties of PEO coatings obtained on titanium alloy in aqueous electrolytes with the additions of NaAlO 2 , Na 3 PO 4 , Na 2 SiO 3 , and KOH have proved that using an electrolyte composition of NaAlO 2 with Na 3 PO 4 offers considerable improvement of the mechanical properties when compared to the ones of the alloy surface before its modification [10]. The presence of anatase and rutile on the alloy surfaces in an aqueous solution of Na 3 PO 4 allowed for potential use in photocatalysis [11].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, it is the studies of the mechanical properties of PEO coatings obtained on titanium alloy in aqueous electrolytes with the additions of NaAlO 2 , Na 3 PO 4 , Na 2 SiO 3 , and KOH have proved that using an electrolyte composition of NaAlO 2 with Na 3 PO 4 offers considerable improvement of the mechanical properties when compared to the ones of the alloy surface before its modification [10]. The presence of anatase and rutile on the alloy surfaces in an aqueous solution of Na 3 PO 4 allowed for potential use in photocatalysis [11].…”
Section: Introductionmentioning
confidence: 98%
“…The maximum error on the peak position was ±0.2 eV. i.e., grooves and ridges, which can be associated with abrading scratches (Qu et al, 2014;Peláez-Abellán et al, 2012). When PAA was electrosynthesized on Ti, the film texture and surface roughness did not change significantly.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 97%
“…In this context, it is essential to evaluate interactions between osteoblastic cells and the biomaterial. Among several surface treatment proposed for Ti implants (Munoz-Castro et al,2009, Valencia-Alvarado et al, 2010, Xiao et al, 2012 oxygen ion implantation represents an effective tool, capable of changing morphology, composition and crystalline phase, as well as mechanical and tribological properties (Oliveira et al, 2011, Savonov et al, 2011Da Silva et al, 2006, Peláez-Abellán et al, 2012. In addition, it has been previously demonstrated that O-PIII treatment improves osseointegration in rat femurs after 3 months of incubation when compared to untreated Ti implants (Mandl et al, 2001;Mandl et al, 2002).…”
Section: Introductionmentioning
confidence: 99%